2008
DOI: 10.1258/jtt.2008.007003
|View full text |Cite
|
Sign up to set email alerts
|

Telepathology training in a master of cytology degree course

Abstract: We have investigated the changes in the workflow of the cytologist due to the introduction of telepathology. These changes occur in two stages. The first is the use of telepathology as a support methodology using external providers (i.e. outside the hospital) to digitize the slides. The second is the use of telepathology in routine laboratory operations using an internal scanner to digitize the slides. To improve courses in the Master of Cytology programme at the University of La Sapienza, new learning modules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
0
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 6 publications
1
6
0
1
Order By: Relevance
“…Digital cytology 1,17-19 integrates medical knowledge and properly designed ICT to investigate the morphological alterations in different degrees of morbidity directly on a digital image (e-slide); it is currently playing an important role in the healthcare system to change and improve the workflows 4,5,20 in the cytology laboratory. The introduction of tablet technology, ranging from cooperative diagnosis up to teleconsulting and telediagnosis, is vital to the evolution of the healthcare system 15,16 for telemedicine and e-health applications of teleimaging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Digital cytology 1,17-19 integrates medical knowledge and properly designed ICT to investigate the morphological alterations in different degrees of morbidity directly on a digital image (e-slide); it is currently playing an important role in the healthcare system to change and improve the workflows 4,5,20 in the cytology laboratory. The introduction of tablet technology, ranging from cooperative diagnosis up to teleconsulting and telediagnosis, is vital to the evolution of the healthcare system 15,16 for telemedicine and e-health applications of teleimaging.…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, e-slides were mainly exchanged using personal computers as clients, which rendered it possible to successfully set up effective networks for teleconsulting and e-learning. 1,4,5 In previous studies 6,7 we showed the importance of using health technology assessment (HTA) tools in telemedicine and ehealth for the assessment of both the acceptance and performance of a telemedicine solution. In 2008, we successfully investigated the acceptance and performance of virtual microscopy using PC platforms with a dedicated HTA tool.…”
mentioning
confidence: 99%
“…igital cytology is a field of digital pathology 1,2 that, through the integration of suitably designed information and communications technologies and medical knowledge, allows the investigation of cellular morphological alterations directly in a digital image called a virtual slide or e-slide [2][3][4] in a cytology e-laboratory. The e-slides are the product of a digitalization workflow produced by means of a heterogeneous process through the use of dedicated scanners starting from a standard microscope slide.…”
mentioning
confidence: 99%
“…Assessment of the introduction of tablet technologies in teleconsulting and e-learning applications will be the focus of future study. 3,4 We trust that stakeholders will focus on this field in order to translate these research experiences into routine and practice.…”
mentioning
confidence: 99%
“…L'enseignement [6,10] bénéficie aussi de cette technologie de transmission. Plusieurs expériences ont déjà été menées ainsi, les échanges rapides entre plusieurs laboratoires de pathologie permettent une aide à la formation à la fois pratique pour les techniques d'immunohistochimie mais aussi théorique par l'analyse des mêmes territoires pathologiques.…”
unclassified